Economic Feasibility Analysis According to Seam Location of Ship Pieces - Hyun-Seong Do; Tak-Kee Lee (한국해양공학회지, 2023)
The structure of a ship is completed by processing various steel plates and welding these plates. This butt welding of plates is defined as a seam in shipyards, and this study seeks to find a way to decrease costs by reducing the utilization of steel through effective seam arrangement. Seams were defined and classified according to purpose, and examples of “pieces” and “main plates” where seam creation had an economical saving effect were selected. For “pieces,” the change in the weight of steel utilized depending on the presence or absence of a seam was calculated, and the resulting change in cost increase was presented. In the case of the “main plate,” the quantity of seams does not change, but an example of cost variation due to the appropriate placement of seams is presented. Hence, a large difference was found in the costs of “pieces” depending on seam location. Thus, it was advantageous to create additional seams. For the “main plate,” it was found that narrow-width and wide-width materials incur more costs. This study demonstrates that creating seams is economically advantageous but may not be preferred owing to the increased workload from a production perspective.